USUL AL-FIQH: ITS EPISTEMOLOGY, PURPOSE, AND USE - Al-Hafizh, Rasyid; ., Fachrul Rozy; Rais, Zaim (DIKTUM: Jurnal Syariah dan Hukum, 2021)
The study of Usul Fiqh only feels essential when it deals with different problems whose orders it executes not involve in the offer of the old Fiqh. Besides that, with the rising number of participants of comparative school legislation alike to discover out which idea is more powerful, since closely as the effort to transform Islamic rule, it will increase appeared in how urgent the role of Ushul Fiqh is. The paper tries to present this discussion to suggest the relevance of this idea of Fiqh in dealing with legal issues dealt with by Muslims who sometimes put on nonessential issues. The author organized research with a comparative descriptive analysis. This study organized a view of the works of Usul Fiqh along with the rules contained there in along with the development of Usul Fiqh and its benefits from time to time. The authors identify that Ushul Fiqh plays a highly considerable position in the improvement of Islamic law. Not merely that, Usul Fiqh, the essential function of Usul Fiqh, is to improve someone to find out the rules they take based on syar'i arguments, so that they do not rely very often on considering other people whose bases they do not have. There are not a few obstacles in the Islamic world community with the presence of discoveries by scientists who require answers and confidence of Islamic law.